Flotillin‐1/2 autoimmunity in a patient with marginal zone lymphoma. Issue 3 (23rd May 2018) - Schuh, Elisabeth; Komorowski, Lars; Feuerecker, Regina; Forstpointner, Roswitha; Straube, Andreas; Kümpfel, Tania
Abstract : The flotillin‐1/2 heterocomplex seems to be a potential autoantigen in a subset of about 1–2% multiple sclerosis (MS) patients. Rarely humoral central nervous system (CNS) autoimmunity against neural surface associated proteins has yet been linked to underlying latent hematologic malignancies. Herein, we demonstrate a case of inflammatory CNS disease with flotillin auto‐antibodies in the context of a marginal zone lymphoma.